Принцип незалежності прокуратури: догматично-правова інтерпретація та правова регламентація - Проневич, О. С.; Pronevych, O. S. (Вісник Харківського національного університету внутрішніх справ. - 2014. - № 4 (67). - С. 6-16, 2014)
Розглянуто догматично-правову інтерпретацію принципу незалежності прокуратури з урахуванням існуючих підходів до доктринального тлумачення правової природи принципів прокурорської діяльності та з особливою акцентуацією уваги на специфіці правової регламентації означеного принципу в титульному законі про прокуратуру. Особливу увагу приділено визначенню основоположних засад теорії правових принципів та європейським стандартам концептуального осмислення і легітимізації принципу незалежності прокуратури.

The article is devoted dogmatic and legal interpretations of the independence of prosecutors considering existing approaches to doctrinal interpretation of the legal nature of the principles and prosecution of accentuation particular attention to the specifics of legal regulation in principle appointed title law prosecutor. The relevance of the topic chosen objectively caused by the adjustment paradigm of organization and functioning of organs, amendment of the legislation on the prosecutor’s office and the consequent deprivation prosecution comprehensive control and supervision competencies and entry into features classic European public prosecution office. Special attention is paid to the definition of the fundamental principles of the theory of legal principles and European standards conceptual understanding and legitimizing the independence of prosecutors. The independence of the prosecutor broadly interpreted as a constitutional principle of justice that involves submission of the prosecutor in the line of force, the Constitution and the laws, and rules out any external pressure and the dependence of the prosecutor. The author stated that the independence of the prosecutor should be considered in the context of conservation of professionalism and responsibility of each prosecutor organs and prosecution as an institution authorized by the implementation of a number of particularly socially important constitutional functions.

Рассмотрена догматично-правовая интерпретация принципа независимости прокуратуры с учётом существующих подходов к доктринальному толкованию правовой природы принципов прокурорской деятельности и с особой акцентуацией внимания на специфике правовой регламентации этого принципа в титульном законе о прокуратуре. Особое внимание уделено определению основ теории правовых принципов и европейским стандартам концептуального осмысления и легитимизации принципа независимости прокуратуры.
The principle of independence of prosecution, dogmatic legal interpretation and legal regulation
Принцип независимости прокуратуры: догматично-правовая интерпретация и правовая регламентация
Проневич, О. С. Принцип незалежності прокуратури: догматично-правова інтерпретація та правова регламентація / О. С. Проневич // Вісник Харківського національного університету внутрішніх справ. - 2014. - № 4 (67). - С. 6-16.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; принцип незалежності прокуратури; прокуратура; principle of independence of prosecution; prosecution; принцип независимости прокуратуры